Retrospective Study on Genetic Diversity and Drug Resistance among People Living with HIV at an AIDS Clinic in Beijing - Yan-Ze Shi; Hui-Huang Huang; Xin-Hua Wang; Bing Song; Tian-Jun Jiang; Min-Rui Yu; Ze-Rui Wang; Rui-Ting Li; Yan-Mei Jiao; Xin Su; Fu-Sheng Wang (MDPI AG, 2024)
(1) Background: The objective of this study was to investigate the prevalence of genetic diversity and drug resistance mutations among people living with HIV (PLWH) attending clinics in Beijing. (2) Methods: A retrospective analysis was conducted on PLWH admitted to the Fifth Medical Center of People's Liberation Army (PLA) General Hospital between 1 March 2013 and 31 July 2020. The participants were analyzed for pretreatment drug resistance (PDR) and acquired drug resistance (ADR). Nested polymerase chain reaction (PCR) was utilized to amplify the pol gene from plasma RNA samples obtained from the participants. Genotypic and HIV drug resistance were determined using the Stanford University HIV Drug Resistance Database. Univariate and multifactorial logistic analyses were used to assess the risk factors for PDR. (3) Results: The overall prevalence rates of PDR and ADR were 12.9% and 27.8%, respectively. Individuals treated with non-nucleoside reverse transcriptase inhibitors (NNRTIs) exhibited the highest prevalence of mutations. Specific mutation sites, such as V179D for NNRTIs and M184V and K65R for nucleoside reverse transcriptase inhibitors (NRTIs), were identified as prevalent mutations. Individuals treated with efavirenz (EFV) and nevirapine (NVP) were found to be susceptible to developing resistance. The multifactorial regression analyses indicated that the factors of circulating recombination form (CRF) genotype CRF07-BC and a high viral load were associated with an increased risk of PDR. CRF01-AE and CRF07-BC were the most prevalent HIV genotypes in our study. (4) Conclusions: The distribution of HIV genotypes in Beijing is complex. There is a need for baseline screening for HIV drug resistance among ART-naive individuals, as well as timely testing for drug resistance among ART-experienced individuals.